In Vitro Drug Metabolism of Green Tea Catechins in Human, Monkey, Dog, Rat and Mouse Hepatocytes - W. Chen, Wendy; Qin, Geng-Yao; Zhang, Ting; Feng, Wan-Yong (Drug Metabolism Letters, 2012)
The metabolic fate of green tea catechins [(-)-epicatechin ((-)-EC), (-)-epicatechin-3-gallate (ECG) (-)- epigallocatechin (EGC) and (-)-epigallocatechin-3-gallate (EGCG)] in cryopreserved human, monkey, dog, rat and mouse hepatocytes was studied. Methylation, glucuronidation, sulfation and isomerization pathways of (-)-EC in all five species were found. Methylation, glucuronidation, sulfation, hydrolysis, isomerization and glucosidation pathways of ECG were found. Species differences in metabolism of (-)-EC or ECG were observed. Surprisingly, no metabolites of EGC or EGCG were detected, but chemical oxidation and polymerization were observed under these experimental conditions. It appeared that enzymatic reactions and chemical reactions were differentiated by an additional hydroxyl group on the B-ring between (-)-EC/ECG and EGC/EGCG. For (-)-EC, thirty-five metabolites including isomerized (M6. M10 and M25), glucuronidated (M3, M5 and M11), sulfated (M7, M15, M16, M18, M20, M23, M26), methylated (M2, M9, M12, M17, M19, M21, M27, M30, M32), glucuronated/methylated (M4, M8, M13, M14), sulfated/methylated (M22, M24, M28, M29, M31, M33, M34, M35) and diglucuronidate (M1), were detected and characterized. M11, M18, M19 and M23 were major metabolites in human hepatocytes; M11, M26 and M31 were major metabolites in monkey hepatocytes; M10, M20, M22, M26 and M31 were major metabolites in dog hepatocytes; M5, M6 and M10 were major metabolites in rat hepatocytes; and M5, M6 and M13 were major metabolites in mouse hepatocytes. For ECG, twelve metabolites including isomerized (M1), hydrolyzed (M3), glucosidated (M2), glucuronidated (M4 and M6), sulfated (M9, M11 and M12), methylated (M7), sulfated/glucuronidated/methylated (M8 and M10) and diglucuronidated (M5), were detected and characterized. M4, M11 and M12 were major metabolites in human hepatocytes; M11 and M12 were major metabolites in monkey hepatocytes; M3 and M11 were major metabolites in dog hepatocytes; M4, M6 and M11 were major metabolites in rat hepatocytes, and M3 was a major metabolite in mouse hepatocytes. The experimental results have demonstrated that fate of catechins in in vitro hepatocytes depends on metabolism and chemical stability. In certain experimental conditions, the chemical reaction may become a dominant pathway.
Keywords: metabolism